Effectiveness of RFID Smart Library Management System / Maizatul Mazni Suhaimi, Zulkifli Mohamed and Nurul Syuhadah Khusaini - Suhaimi, Maizatul Mazni; Mohamed, Zulkifli; Khusaini, Nurul Syuhadah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Libraries are crucial for diverse resources, particularly for students and educators. The Library Management System (LMS) in Perpustakaan Raja Tun Uda (PRTU) still used barcode technology, which was inadequate and could increase the workload of the librarians. This study presented the development and evaluation of the Smart Portable Library Management System (SPLMS) using RFID technology. The study addressed the gap in the literature by focusing on the impact of angle adjustment on the performance of UHF RFID readers in reading RFID tags placed on book spines. The study was conducted by implementing the SPLMS and performing system testing at different angles. The scope of the study encompassed the design and implementation of the SPLMS, system testing with varying angles, and evaluation of the reader's success rate in reading RFID tags. The validation of ZK-RFID101 of the results have shown that the reader has a 100% success rate for distances between 1 and 3 meters, but the success rate drops to 80% at 5 and 6 meters due to radio frequency interference. The main findings indicated that increasing the angle from 0 to 90-degrees improved the reader's performance, although certain tags still presented challenges. The results from the five conducted trials strongly indicated that a 90-degree angle was the optimum performance. The study concluded that the angle and placement of RFID readers was crucial for optimal performance in library management systems. The SPLMS provided librarians with a user-friendly dashboard for efficient book collection management, boosting productivity and enhancing user experience.